2009
DOI: 10.1073/pnas.0909218106
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to DNA damage in plant stem cell niches

Abstract: The growing apices of plants contain stem cells that continually produce tissues, which, in the shoot, include the germline. These stem cell populations remain active throughout the plant's life, which can last for centuries, and are particularly exposed to environmental hazards that cause DNA damage and mutations. It is not known whether plants have mechanisms to safeguard the genome specifically in these crucial cell populations. Here, we show that root and shoot stem cells and their early descendants are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
254
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(266 citation statements)
references
References 42 publications
11
254
1
Order By: Relevance
“…Two recent reports have shown that Arabidopsis root and shoot stem cells and their descendants undergo cell death upon DNA damage (12,28). In the stem cell niche, programmed cell death may be a viable way to remove DNA-damaged cells, but here we found that DSBs induced early onset of endoreduplication in the transition zone of roots and the sepal epidermis.…”
Section: Discussionmentioning
confidence: 29%
See 2 more Smart Citations
“…Two recent reports have shown that Arabidopsis root and shoot stem cells and their descendants undergo cell death upon DNA damage (12,28). In the stem cell niche, programmed cell death may be a viable way to remove DNA-damaged cells, but here we found that DSBs induced early onset of endoreduplication in the transition zone of roots and the sepal epidermis.…”
Section: Discussionmentioning
confidence: 29%
“…To identify plant-specific mechanisms underlying the genotoxic stress response, we first observed Arabidopsis roots that had been exposed to the radiomimetic reagent zeocin (11,12). When seedlings were transferred to 10-μM zeocin plates, root growth was arrested, and cyclin B1 expression (indicative of progression into G2) was reduced ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned processes are regulated by positional signals (Heidstra and Sabatini, 2014). Cell-type-specific programmed cell death (PCD) has been observed in root meristems of the model plant Arabidopsis (Arabidopsis thaliana) after exposure to IR, radiomimetic chemicals, UV (Curtis and Hays, 2007;Furukawa et al, 2010;Fulcher and Sablowski, 2009), and chilling stress (Hong et al, 2017). This programmed response requires SOG1, ATM, and (to a lesser degree) ATR as well as de novo protein synthesis (Furukawa et al, 2010).…”
mentioning
confidence: 99%
“…The growth of At13 lines was comparable to wild-type controls, suggesting their proficiency in DNA repair. Plant growth retardation in response to genotoxic stress is caused by preferential cell death of stem cells in meristematic tissues, and Ku deficiency exacerbates this sensitivity (Fulcher and Sablowski, 2009). Therefore, we quantified cell death in the root apical meristem of At18 plants 24 h after treatment with high doses of bleomycin ( Figures 3C and 3D).…”
Section: Partially Impaired Dna Binding Renders the Ku Complex Dysfunmentioning
confidence: 99%